PELATIHAN PEMBUATAN KEMASAN SABUN BUNGA MATAHARI DI DESA BOJONGHALEUANG SEBAGAI PROGRAM COMMUNITY EMPOWERMENT - Dewi Isma Aryani; Nina Nurviana; Heddy Heryadi (Jurnal Kewirausahaan dan Bisnis, 2020)
Maranatha Christian University as a private university in Bandung has a work program that is reflected in the vision and mission of higher education tri dharma. The vision and mission of Maranatha Christian University which is carried out through the fields of teaching, research, and community service, one of which is focused on community empowerment programs and social problems around, involving several teaching staff (lecturers) from representatives of the Visual Communication Design Study Program and D-3 Art Design as a material formulator as well as a skills trainer or teacher as a form of social responsibility. The community service program which was initiated in the form of training on making soap product packaging from sunflower materials creatively and has aesthetic value was carried out by providing materials online and practicing packaging directly to the training participants for five meetings. This activity is targeted at community partners who are not economically productive yet, such as the Kota Baru Parahyangan (KBP) assisted community groups that are members of the Maju Bersama Sejahtera Joint Business Group (KUBE). The potential of KUBE Maju Bersama Sejahtera in Bojonghaleuang Village, West Bandung Regency is sunflower and the honey bee. The processing and utilization of sunflower seeds as herbal soap material need to be supported by the creative efforts of KUBE Maju Bersama Sejahtera to package sunflower soap products in a unique, attractive, and marketable way. This community service activity succeeded in providing insight into the packaging technique for soap products from sunflower to the Maju Bersama Sejahtera Joint Business Group (KUBE) as a provision for home industry skills that can support the household economy. These results can be seen after participating in the activity, the participants can make various forms of packaging in a unique and creative way.Keywords: community empowerment, creative, packaging, soap, sunflower